Penerapan Model Pembelajaran Problem Based Learning Untuk Meningkatkan Hasil Belajar Siswa Pada Mata Pelajaran PAI - Handayani, Sutri (EduSpirit : Jurnal Pendidikan Kolaboratif, 2025)
This study aims to improve students’ learning outcomes and engagement in learning Surat at-Tiin using the Problem-Based Learning (PBL) model in the 4th-grade class at SDN 03 Kuamang, Panti District. The research was conducted in two cycles, each consisting of planning, implementation, observation, and reflection stages. The results showed that in Cycle I, the students’ learning completeness reached only 72%, while in Cycle II, it increased to 92.3%. Students’ engagement also increased, with 61.5% of students classified as very active. This improvement demonstrates that the implementation of the PBL model can enhance students’ learning outcomes and engagement, as well as help students better understand the content of Surat at-Tiin